2010
DOI: 10.1590/s1516-84842010005000086
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte glucose-6-phosphate dehydrogenase deficiency in male newborn babies and its relationship with neonatal jaundice

Abstract: Deficiência de glicose-6-fosfato desidrogenase eritrocitária em recém-nascidos do sexo masculino e sua relação com a icterícia neonatal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
3
Order By: Relevance
“…On the other hand, G6PDd was detected in 3.4% of male new-borns with NNJ in the absence of foetal-maternal incompatibility in Costa Rica [ 59 ] and in 69.6% of a group of neonates who had unexplained moderate to severe jaundice [ 60 ]. Four studies reported no severe complications in G6PD-deficient new-borns with NNJ [ 53 , 54 , 56 , 59 ], while three works described the need for exchange transfusions [ 50 , 51 , 55 ], three described the occurrence of kernicterus [ 51 , 60 , 61 ], and two described fatal outcomes [ 29 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, G6PDd was detected in 3.4% of male new-borns with NNJ in the absence of foetal-maternal incompatibility in Costa Rica [ 59 ] and in 69.6% of a group of neonates who had unexplained moderate to severe jaundice [ 60 ]. Four studies reported no severe complications in G6PD-deficient new-borns with NNJ [ 53 , 54 , 56 , 59 ], while three works described the need for exchange transfusions [ 50 , 51 , 55 ], three described the occurrence of kernicterus [ 51 , 60 , 61 ], and two described fatal outcomes [ 29 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…A serious life‐threatening manifestations of G6PD deficiency can be seen in the neonatal period including early and late onset hyperbilirubinemia (neonatal jaundice), risk of kernicterus, death, and spastic cerebral palsy . Several studies have shown that the risk of neonatal jaundice is much greater in G6PD‐deficient neonates than in non‐deficient neonates . The American Academy of Pediatrics considers G6PD deficiency as a key etiologic risk factor for the development of severe hyperbilirubinemia and kernicterus, and the enzyme deficiency was found to increase the severity of prognosis of kernicterus among infants.…”
Section: G6pd Deficiencymentioning
confidence: 99%
“…A Glucose 6-fosfato desidrogenase (G6PD) é uma enzima encontrada em todas as células do corpo. Catalisadora da primeira etapa na via da pentose fosfato, com a função de proteger as células contra danos oxidativos, a G6PD converte a coenzima Nicotinamida Adenina Dinucleotídeo Fosfato (NADP) em sua forma reduzida Nicotinamida Adenina Dinucleotídeo reduzida (NADPH), sendo, praticamente, toda fonte geradora de NADPH, que tem como função combater os efeitos prejudiciais das espécies reativas de oxigênio (IGLESSIAS MAC, et al, 2010).…”
Section: Introductionunclassified
“…Universidade do Vale do Sapucaí (UNIVAS), Pouso Alegre -MG 6. Faculdade de Minas (FAMINAS), Belo Horizonte -MG 7. Universidade Federal do Amapá (UNIFAP), Macapá -AP.…”
unclassified